Short Communication: Effect of mulching materials on mini-tuber production of potato fromin vitroplantlets - D.A.N. MAJUMDER; S.C. NATH; M.A. KABIR; S. MAJUMDER (Smujo International, 2016)
Abstract. Majumder DAN, Nath SC, Kabir MA, Majumder S. 2016. Effect of mulching materials on mini-tuber production of potato from in vitro plantlets. Nusantara Bioscience 8: 123-127. This paper describes the effectiveness of organic and plastic mulching for potato mini-tuber production in Bangladesh. The field experiment was carried out during the Rabi season of 2013-2014 to 2014-2015 with virus-free in vitro cultured plantlets of var. Diamant. The mulching materials of water hyacinth mulch (WHM), rice straw mulch (RSM) and black polythene mulch (BPM) were compared with no-mulching (control) to find out suitable mulching material (s) for obtaining higher tuber yield. During the whole production period morphological characters, yield characters as well as of soil temperature and soil moisture were assessed. The results showed that WHM (5.28 t/ac) and RSM (4.59 t/ac) had a positive effect on increased the proportion of tuber size above 28 mm and on increasing of tuber yields by 54.0% to 77.2% compared with control (2.98 t/ac). Higher soil temperatures were recorded with plastic mulch caused lower potato tuber yield (3.04 t/ac) while WHM and RSM decreased soil temperatures and increased the moisture percentage. The mulching of mini tubers had negative effect on tubers quality in regards to scab, green tuber, and weed biomass.